Performance of the timed "up & go" test in spinal muscular atrophy. Issue 2 (12th May 2014) - Dunaway, Sally; Montes, Jacqueline; Garber, Carol Ewing; Carr, Brendan; Kramer, Samantha S.; Kamil‐Rosenberg, Shirit; Strauss, Nancy; Sproule, Douglas; De Vivo, Darryl C.
ABSTRACT Introduction The timed "up & go" (TUG) test is a quick measure of balance and mobility. TUG scores correlate with clinical, functional, and strength assessment and decline linearly over time. Reliability and validity have not been tested in spinal muscular atrophy (SMA). Methods: Fifteen ambulatory SMA participants performed TUG testing and strength, functional, and clinical assessments. Intraclass correlation coefficients quantified test–retest reliability. Convergent validity was determined using Pearson correlation coefficients. Results: Test–retest reliability was excellent for all participants. TUG was associated significantly with total leg and knee flexor strength, as well as the Hammersmith Functional Motor Scale Expanded, the 10‐meter walk/run, and 6‐minute walk tests. TUG findings were not associated with knee extensor strength, pulmonary function, or fatigue. Conclusions: In SMA, the TUG test is easily administered, reliable, and correlates with established outcome measures. TUG testing is a potentially useful outcome measure for clinical trials and a measure of disability in ambulatory patients with SMA. Muscle Nerve 50:273–277, 2014